Effects of vasopressors on circulation in the porcine abdominal island flap model. Issue 10 (October 2019) - Chung, Jae-Ho; Cheon, Jeong-Hyun; Kim, Min-Sook; Min, Doo-Jae; Yoon, Eul-Sik; Lee, Byung-Il; Park, Seung-Ha; Kim, Deok-Woo
Summary: Background: During reconstructive surgical procedures, systemic vasopressors are frequently used to maintain normal blood pressure. However, questions have arisen regarding the pharmacologic effects of vasopressors on flap circulation. Many plastic surgeons have expressed concern about the possibility of impaired flap circulation caused by the vasoconstrictive effect of the drugs. However, the opposing argument exists that the increase in mean arterial pressure from vasoactive agents may improve flap perfusion. The purpose of this study was to evaluate the effect of commonly used vasopressors on flap circulation. Methods: The vertical rectus abdominis myocutaneous (VRAM) island flap was raised in five female pigs (38.2∼40.7 kg). Hemodynamic parameters were measured continuously by a carotid arterial catheter. A bi-directional transonic vascular doppler flow probe and Laser Doppler perfusion monitor (LDPM) unit were applied to record the continuous change in pedicle artery flow and microvascular perfusion following intravenous administration of dopamine (3, 5, 10µg/kg/minute), dobutamine (1.25, 2.5, 5µg/kg/minute), and norepinephrine (0.05, 0.1, 0.2µg/kg/minute). Results: Both microvascular perfusion and pedicle flow were generally proportional to the mean arterial pressure, and all three vasopressors improved flap perfusion and pedicle flow without deleterious effects. Norepinephrine showed the highest microvascular perfusion and dobutamine showed the highest pedicle flow rate. The mean blood pressure was the only statistically significant factor to affect both microvascular perfusion and pedicle flow ( p < 0.0001). Conclusion: Our results strongly suggest that the foremost three vasopressors can be used for flap surgery without deterioration, and that the maintenance of adequate systemic blood pressure is crucial for good flap circulation.